2015
DOI: 10.1016/j.appet.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Infant and maternal predictors of early life feeding decisions. The timing of solid food introduction

Abstract: There is limited research on the maternal and infant characteristics associated with the timing of solid food introduction. The current study examined how maternal feeding style and infant temperament independently and interactively predicted the age at which infants were introduced to solid food. Data from 115 predominately white, middle-class mothers were collected when infants were 4 and 6 months of age. The timing of solid food introduction was positively correlated with mothers' age, education, breastfeed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 48 publications
(69 reference statements)
8
44
2
4
Order By: Relevance
“…Turning to research in the context of developed countries, several prior research studies have found that younger mothers have a higher likelihood of early complementary feeding [ 21 ]. The findings of a recent study in the United States context were in agreement, having identified a positive association between the timing of the introduction of solid foods and the age of the mother [ 26 ].…”
Section: Discussionsupporting
confidence: 65%
“…Turning to research in the context of developed countries, several prior research studies have found that younger mothers have a higher likelihood of early complementary feeding [ 21 ]. The findings of a recent study in the United States context were in agreement, having identified a positive association between the timing of the introduction of solid foods and the age of the mother [ 26 ].…”
Section: Discussionsupporting
confidence: 65%
“…Mothers of infants who were perceived to have difficult temperaments were more likely to give their infants food in order to calm them (McMeekin et al, 2013). Negative infant reactivity and maternal use of the pressuring with cereal feeding style was found to be associated with earlier introduction of solid foods (Doub, Moding, & Stifter, 2015). These infant characteristics may also operate in conjunction with maternal psychosocial characteristics to influence feeding styles.…”
Section: Introductionmentioning
confidence: 99%
“…Weaning should therefore continue as freely to facilitate nutritional fate and the child's somatic and behavioural development. 27 N o n -c o m m e r c i a l u s e o n l y…”
Section: Discussionmentioning
confidence: 99%